The Effect of Apparatus Competence and Supervision on the Accountability of Village Fund Management (Study on villages in Mootilango District, Gorontalo Regency) - Yusgiantoro Yusgiantoro; Harun Blongkod; Lukman Pakaya (International Journal of Economics Studies, 2026)
The Influence of Apparatus Competence and Supervision on the Accountability of Village Fund Management (Study on Villages in Mootilango District, Gorontalo Regency). Thesis of the Department of Accounting, Faculty of Economics and Business, Gorontalo State University. Under the guidance of Mr. Dr. Harun Blongkod, S.Pd., S.Ak., MSA as supervisor I and Mr. Lukman Pakaya, S.Pd, MSA as supervisor II. This study aims to analyze the influence of apparatus competence and supervision on the accountability of village fund management in villages in Mootilango District, Gorontalo Regency. Accountability in the management of village funds is an important factor in ensuring effectiveness, efficiency, and transparency in the use of village funds provided by the central government. Good apparatus competence is expected to improve the quality of village fund management, while strict supervision is expected to reduce potential irregularities in the use of the village budget. The results of the study show that the competence of the apparatus has a significant influence on the accountability of village fund management. Meanwhile, supervision also has a positive and significant effect on the accountability of village fund management. These findings confirm that the higher the competence of the apparatus and the better the supervision system implemented, the level of accountability in the management of village funds will also increase.